1982
DOI: 10.1366/0003702824639556
|View full text |Cite
|
Sign up to set email alerts
|

Librational Modes of Water in Zinc Formate Dihydrate

Abstract: The infrared spectra of zinc formate dihydrate are presented for the region 1000 to 400 cm−1 along with the laser-excited Raman spectra. With the use of the corresponding IR and Raman spectra for the deuterated and anhydrous samples and their temperature dependence (between 300 to 90 K), two sets of bands for the in-plane bending mode of formate ion and all the three librations of water have been identified corresponding to two types of formate and water in the unit cell. The large shift of the formate ν3 mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The assignments of the bands are done by analogy with those of metal formate dihydrates. (HEYNS, 1985 (a) (b), TEWARI et al, 1982TEWARI et al, , 1983.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assignments of the bands are done by analogy with those of metal formate dihydrates. (HEYNS, 1985 (a) (b), TEWARI et al, 1982TEWARI et al, , 1983.…”
Section: Resultsmentioning
confidence: 99%
“…2 the infrared spectra of the double salts in the range .of 900-400 cm-' are shown where the v3 modes of HCOO groups and the librational modes of the water molecules occur. As far as v3 is concerned, studies on Cu(HC00)2.2 H20 (HEYNS, 1985 (a)) and Zn(HC00)2 -2 H20 (TEWARI et al, 1982) have been revealed that existensive coupling occurs between v3 mode and the librations of the water molecules. The two bands in the frequency range of 760-785 cm-' are attributed to v3 modes of the formate groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of preparation of samples and recording of ir and Raman spectra have been described elsewhere (4). The accuracy in the measurement of band positions is "4 cm-I, while the estimated half-widths and relative intensities are dependable within 20% for the OH stretching region.…”
mentioning
confidence: 99%